The Minangkabau Khatam Al-Qur’an Tradition (Negotiating Spirituality and Technology in the Digital Age) - Riri Maiyati; Ismiati Ismiati; Rahma Ghania Alhafiza (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
The tradition of completing the recitation of the Qur’an in Minangkabau serves as a milestone in religious transition and a vital anchor of communal identity. However, the current penetration of digital screen culture is significantly undermining this local tradition. Previous studies have largely explored digital piety at the macro level but have overlooked how communal celebrations systematically negotiate their core values in the face of public screen exposure. This study aims to analyze how spirituality and technology are negotiated in the mediatization of khatam celebrations in West Sumatra. Through a qualitative ethnographic approach conducted from May to June 2025 in Bukittinggi, Agam, and Tanah Datar, this study involved 30 key informants (religious scholars, TPA teachers, ninik mamak, parents, and khatam participants). Data were collected through participatory observation, in-depth interviews, and digital visual tracking. The main argument is that the digital transformation of the khatam ceremony does not signify the extinction of tradition, but rather a multi-layered negotiation toward a dynamic cultural equilibrium. Empirical findings reveal that digital mediatization offers opportunities for permanent documentation and diaspora connectivity, while simultaneously raising challenges related to concerns about visual prestige, spiritual shallowness, and cultural commodification. These pressures drive active negotiations: religious scholars safeguard the sanctity of texts, families compromise piety for social status, and adolescents develop hybrid forms of spirituality. Theoretically, this study expands the field of digital religion studies by framing the mediatization of religious celebrations as an arena of active technological negotiation, rather than passive cultural decay.